2019
DOI: 10.1002/ijc.32111
|View full text |Cite
|
Sign up to set email alerts
|

Association of type and intensity of physical activity with plasma biomarkers of inflammation and insulin response

Abstract: Several biological mechanisms linking physical activity with cancer have been proposed. However, the influence of specific components of physical activity (volume, type and intensity), and their interaction with adiposity and diet, on cancer‐related biomarkers remain unclear. We used cross‐sectional data on 7,219 men in the Health Professionals Follow‐up Study (1992–1994) with C‐reactive protein (CRP), interleukin‐6 (IL6), tumor necrosis factor alpha receptor 2 (TNFαR2), adiponectin, C‐peptide and triglyceride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 44 publications
0
19
0
1
Order By: Relevance
“… 44 A large cross-sectional study in cancer-free men has shown that engaging in mostly moderate-intensity activity, with preferably combined aerobic and resistance exercises rather than aerobic only, was associated with improved inflammatory biomarkers and insulin response. 45 Yet, the amount of PA and the modalities of practice needed to modify cancer- and treatment related biomarker changes in breast cancer patients undergoing adjuvant therapy have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“… 44 A large cross-sectional study in cancer-free men has shown that engaging in mostly moderate-intensity activity, with preferably combined aerobic and resistance exercises rather than aerobic only, was associated with improved inflammatory biomarkers and insulin response. 45 Yet, the amount of PA and the modalities of practice needed to modify cancer- and treatment related biomarker changes in breast cancer patients undergoing adjuvant therapy have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Person-time was assessed as months of follow-up from the return date of the 1988 questionnaire until incident CVD, death, or the end of follow-up (31 May 31 2008), whichever came first. We used time-varying Cox proportional hazards models to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) for the associations between 24-month average ambient PM 2:5 exposure [per 10 lg=m 3 increase (Hart et al 2015b;Puett et al 2009) or by quintiles of PM 2:5 exposure], physical activity [per 9 METh/wk for overall physical activity, based on weekly physical activity recommendations (Lee et al 2019; U.S. Department of Health and Human Services 2019) or by quartiles of overall physical activity, walking, and vigorous activity], and the multiplicative interaction of the two on risk of MI, stroke, MI or stroke combined, and overall mortality. We accounted for missing covariate data using missing indicators.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated overall physical activity in MET-hours per week by summing the MET-hours per week across all activities. Additionally, we considered MET-hours per week from walking alone, MET-hours per week from vigorous-intensity activities ( : jogging, running, biking, swimming, and tennis), MET-hours per week from low- or moderate-intensity activities ( ) ( Lee et al. 2019 ; U.S. Department of Health and Human Services 2019 ), and MET-hours per week for physical activities likely to be performed outdoors (e.g., walking, running, biking, lawn mowing), created by excluding activities more likely to be performed indoors (squash, racquet ball, arm weight training, leg weight training) from total MET-hours.…”
Section: Exposure Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…En un amplio estudio epidemiológico realizado en Brasil, la práctica regular de al menos 150 minutos/ semana de actividad física vigorosa se asoció a niveles significativamente más altos de HDLc y más bajos de triglicéridos (34) . En el Health Professionals Follow-up Study (HPFS), un estudio de cohorte prospectivo de hombres estadounidenses, la diferencia en la relación TG/HDLc entre los quintiles superior e inferior de la práctica de actividad física fue -26 % (35) .…”
Section: Impacto Del Ejercicio Sobre Los Triglicéridos Plasmáticosunclassified